2021
DOI: 10.1186/s12864-021-08213-w
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome comparative analysis of ovarian follicles reveals the key genes and signaling pathways implicated in hen egg production

Abstract: Background Ovarian follicle development plays an important role in determination of poultry egg production. The follicles at the various developmental stages possess their own distinct molecular genetic characteristics and have different biological roles in chicken ovary development and function. In the each stage, several genes of follicle-specific expression and biological pathways are involved in the vary-sized follicular development and physiological events. Identification of the pivotal ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 98 publications
(115 reference statements)
1
14
0
Order By: Relevance
“…This is consistent with previously reported results ( Mishra et al, 2020 ). The genes enriched in the BP category of this study, including GABRA1, LPAR2 , and ATF3 , which have been reported to be possibly involved in regulating egg-laying performance( Bello et al, 2021 ; Chen et al, 2021 ), and GABRA1 can inhibit the proliferation of granulosa cells and stimulate apoptosis ( Sun et al, 2021 ).…”
Section: Discussionmentioning
confidence: 82%
“…This is consistent with previously reported results ( Mishra et al, 2020 ). The genes enriched in the BP category of this study, including GABRA1, LPAR2 , and ATF3 , which have been reported to be possibly involved in regulating egg-laying performance( Bello et al, 2021 ; Chen et al, 2021 ), and GABRA1 can inhibit the proliferation of granulosa cells and stimulate apoptosis ( Sun et al, 2021 ).…”
Section: Discussionmentioning
confidence: 82%
“…Studies have shown that GABRA1 plays an important role in egg production. High expression levels of GABRA1 can inhibit the proliferation of granulosa cells, enhance cell apoptosis, and inhibit the synthesis and secretion of progesterone, resulting in reduced egg production [43][44][45]. The egg-laying rhythm of laying hens is a neuromodulatory process [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report, this gene was found to be associated with granulosa cell proliferation and apoptosis in the ovary [ 21 ]. However, Sun et al found that it may be at the GWF developmental stage and that high VIPR2 expression may be associated with brooding and lower egg-laying traits in hens [ 31 ]. In this study, it was found to have higher expression in high egg-laying ovaries and may have a positive effect on egg production.…”
Section: Discussionmentioning
confidence: 99%